Ten days in a mad-house - Ricca, Brad (Gallery 13, 2022)
"While working for Joseph Pulitzer's newspaper in 1887, Nellie Bly began an undercover investigation into the local woman's lunatic asylum on Blackwell's Island. Intent on seeing what life was like on the inside, Bly fooled trained physicians into thinking she was insane--a task too easily achieved--and had herself committed. In her ten days at the asylum, Bly witnessed horrifying conditions: the food was inedible, the women were forced into labor for the staff, the nurses and doctors were cruel or indifferent, and many of the women held there had no mental disorder of any kind. Now adapted into graphic form by Brad Ricca and vividly rendered with beautiful and haunting illustrations by Courtney Sieh, Bly's bold venture is given new life and meaning, as her fearless scrutiny into the living conditions at Blackwell's asylum forever changed the field of journalism. A timely reminder to take notice of forgotten populations, Then Days in a Mad-House warns us what happens when we decide to look away"--